Serological profile of HSV-2 in patients attending STI clinic: Evaluation of diagnostic utility of HSV-2 IgM detection - Choudhry Shilpee; Ramachandran V; Das Shukla; Bhattacharya S; Mogha Narendra (Wolters Kluwer Medknow Publications, 2009)
Objective: The present study was done to evaluate the serological profile of herpes simplex virus-2 (HSV-2) among patients attending sexually transmitted infections (STI) clinic and to determine the utility of detecting HSV-2 IgM antibodies in such patients. A correlation of HSV-2 infection with other STI including HIV has also been attempted. Materials and Methods: Hundred consecutive patients who attended STI clinic, with one or more of the complaints as enunciated by WHO in syndromic approach for the diagnosis of STI, were included as subjects. All subjects were screened for common STI by standard laboratory procedures/ commercially available kits. HSV-1 and HSV-2 IgM antibody was detected by commercially available enzyme immuno assay kit in all patient′s sera. Sera were also tested for other STI, namely HIV, Hepatitis B virus, Hepatitis C virus and Treponema pallidum. Antigen detection for Chlamydia trachomatis was done in genital swabs of all patients by Bio-Rad Chlamydia Microplate EIA 31189 (United States) kit. Results: Thirty patients were found to have genital herpes. In 17/30 (56.6%) patients, HSV-2 serology was found to correlate with the clinical diagnosis. The coexistence of other infection in HSV-2 seropositive patients was detected in 8/30 patients. None of the patients having concomitant infections were clinically diagnosed accurately. Sensitivity, specificity, positive predictive value and negative predictive value of IgM antibodies for the diagnosis of genital herpes was 73.91%, 90.91%, 70.83% and 92.91% respectively. Conclusion: HSV-2 IgM detection could only be used as a supportive test for the diagnosis of genital herpes . It needs to be emphasized that the sensitivity and positive predictive value scores are pointers for further improvement in the commercial assay systems and a large sample size may determine the broader utility of such systems.